ANESTHETIC CONSIDERATIONS FOR CRITICALLY ILL PATIENTS WITH SEPSIS - SIROHI, DIKSHA; KUMAR, DINESH; CHOUDHARY, RANU (International Journal of Current Pharmaceutical Research, 2025)
Objective: Sepsis is a life-threatening condition characterized by organ dysfunction due to a dysregulated host response to infection. Critically ill patients with sepsis often require surgical interventions, presenting significant anesthetic challenges due to profound physiological alterations and multiple organ dysfunctions. Methods: This systematic review aims to synthesize current evidence on anesthetic management strategies for critically ill patients with sepsis. A comprehensive literature search was conducted in PubMed, Embase, and Cochrane Library databases for studies published up to October 2023. Inclusion criteria encompassed clinical trials, observational studies, reviews, and guidelines focusing on anesthetic considerations in septic patients. Results: Key findings indicate that thorough preoperative assessment, vigilant hemodynamic monitoring, careful selection of anesthetic agents, and tailored ventilatory strategies are crucial for improving perioperative outcomes. Hemodynamic instability necessitates the use of invasive monitoring and vasoactive medications like norepinephrine. Etomidate and ketamine are preferred induction agents due to their hemodynamic stability, with considerations for their side effects. Maintenance anesthesia often favors total intravenous techniques to minimize cardiovascular depression. Protective lung ventilation strategies are essential due to the high risk of acute respiratory distress syndrome (ARDS). Postoperative care requires multidisciplinary collaboration to manage ongoing sepsis and prevent complications. Conclusion: This review highlights the importance of individualized anesthetic plans and suggests that adherence to evidence-based practices can enhance patient outcomes in this high-risk group.